Diversity of Haemogregarine Parasites Infecting Brazilian Anurans, with a Description of New Species of Dactylosoma (Apicomplexa: Adeleorina: Dactylosomatidae) - Úngari, Letícia Pereira [UNESP]; Netherlands, Edward Charles; Santos, André Luiz Quagliatto; de Alcantara, Edna Paulino [UNESP]; Emmerich, Enzo [UNESP]; da Silva, Reinaldo José [UNESP]; O´Dwyer, Lucia Helena [UNESP] (Springer Nature, 2022)
Purpose: Brazilian anurans are considered the most diverse and species rich around the world. Although in recent years there has been a strong focus on research related to this group of animals, their parasites have not received the same attention. Thus, this study aimed to provide morphological and molecular data on haemogregarines biodiversity infecting Brazilian anurans. Methods: During 2020, 116 anurans were collected from four Brazilian States and their blood and fragment of organs were screened for haemogregarine parasites. Results: From the total, seven (6.03%) animals were found infected with species of Hepatozoon and Dactylosoma. Based on the morphological and molecular analysis, four anurans were found infected with Hepatozoon latrensis. The phylogenetic analysis has shown the isolates from this study grouping with the Brazilian anuran Hepatozoon clade, also with gene similarity ranging from 99.70 to 100% to H. latrensis isolates available on GenBank. Furthermore, three specimens (Trachycephalus typhonius, Leptodactylus latrans, and Rhinella diptycha) were infected with the same species of Dactylosoma (100% genetic similarity), with a genetic similarity of 98.56% to Dactylosoma piperis the only other species described in Brazil. In support of the molecular data, different morphological characters were observed in the blood smears as compared to D. piperis, suggesting that the species of Dactylosoma from the present study infecting three different species of Brazilian anurans is an undescribed species. Conclusion: Thus, this study increases the knowledge of Brazilian anuran blood parasites and demonstrates the importance of using integrative approaches for the diagnosis of haemoparasites.
Keywords: 18 S rRNA; Amphibian; Haemogregarine; Haemoparasite; Hepatozoon; Phylogeny